Averaged strain energy density-based synthesis of crack initiation life in notched steel bars under torsional fatigue (Fracture and Structural Integrity, 2016)
The torsional fatigue behaviour of circumferentially notched specimens made of austenitic stainless steel, SUS316L, and carbon steel, SGV410, characterized by different notch root radii has been recently investigated by Tanaka. In that contribution, it was observed that the total fatigue life of the austenitic stainless steel increases with increasing stress concentration factor for a given applied nominal shear stress amplitude. By using the electrical potential drop method, Tanaka observed that the crack nucleation life was reduced with increasing stress concentration, on the other hand the crack propagation life increased. The experimental fatigue results, originally expressed in terms of nominal shear stress amplitude, have been reanalysed by means of the local strain energy density (SED) averaged over a control volume having radius R0 surrounding the notch tip. To exclude all extrinsic effects acting during the fatigue crack propagation phase, such as sliding contact and/or friction between fracture surfaces, crack initiation life has been considered in the present work. In the original paper, initiation life was defined in correspondence of a 0.1÷0.4-mm-deep crack. The control radius R0 for fatigue strength assessment of notched components, thought of as a material property, has been estimated by imposing the constancy of the averaged SED for both smooth and cracked specimens at NA = 2 million loading cycles.
Keywords: Torsional fatigue; Notch effect; Crack initiation; Averaged SED; Electrical potential drop